PERAN ORANG TUA DALAM PENERAPAN PENDIDIKANAGAMA DAN MORAL BAGI ANAK - Nuraini . (MUADDIB Jurnal Kependidikan dan Keislaman, 2013)
education is the process of instruction and training, its the first element of the definition needs no exlanation, discipline is the education of wildness, instruction is the cultivation of the volitional and cognitive faculties. Man is the only creature that must be educated by education we mean care (maintenance) discipline (training) andinstruction, including culture. Man can become man throught education only what education makes him. so, parents is the first and crucial trainer in making character of their child.and the importance of example in the evelopment of ethical values and religious attitudes, the importance of model to be imitated and identified with, of a dynamic, popular teacher, adevoted, knowledgeable, warm person, the kids love and respect.